(untitled) (Bangladesh Journal of Medical Science, 2018)
Objective: Plants play valuable role in the new drug discovery and significantly used to treat different diseases. Nowadays scientists are investigating the therapeutically active phytochemical constituents that are safe and producing lesser side effect in comparative to other standard drugs. Methods: The plant Holoptelea integrifolia is medicinally important and this study was carried out to evaluate the anti inflammatory activity of aqueous extract of the leaves of Holoptelea integrifolia in male albino rats wistar stain treated with acetic acid to induced paw edema. Results: Result indicated the significant anti-inflammatory activity while compared with standard drug (diclofenac sodium).Brine shrimp bioassay (cytotoxicity), phytotoxicity, insecticidal and enzyme inhibition activity was performed in different extracts of the leaves of H. integrifolia. Results of brime shrimp bioassay indicating positive lethality at high dose in BuOH and H2O only. While the results of phytotoxicity in all crude extracts displayed mild phytotoxicity(46.3 µg/ml) in high concentrations (1000 µg/ml) except H2O extract showed no phytotoxicity. Result of insecticidal activity revealed that BuOH extract were found more effective against Rhyzoperthadominica, the EtOH extract expressed major while EtOAC extract showed mild activity against Callosobruchusanalis. Aqueous extract possessed no insecticidal activity. Conclusion: Results of Urease inhibition activity suggested that EtOAC and BuOH extracts of this plant expressed no activity while EtOH and H2O possessed mild inhibiting activity. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.212-217